Exploring the relationships among teacher–student dynamics, learning enjoyment, and burnout in EFL students: the role of emotional intelligence - Li, Ying; Zhang, Li (Frontiers in Psychology, 2024)
Amidst the academic challenges faced by Chinese English as a Foreign Language (EFL) students, this research investigates the intricate dynamics between teacher-student relationships, learning enjoyment, and burnout, aiming to unravel the role of emotional intelligence as a potential mediator. Delving into the experiences of 806 EFL students, this study employs Structural Equation Modeling (SEM) to scrutinize these relationships comprehensively. The objectives include unveiling the correlations among teacher-student dynamics, learning enjoyment, and burnout, while elucidating the mediating influence of emotional intelligence. The findings elucidate robust connections between positive teacher-student relationships, heightened learning enjoyment, and reduced burnout levels among EFL students. Notably, the study uncovers the pivotal role of emotional intelligence as a mediator, offering insights into how teacher-student relationships and learning enjoyment impact burnout. These outcomes emphasize the significance of nurturing students' emotional intelligence as a shield against burnout, advocating for tailored educational interventions. Ultimately, this research advocates for proactive measures to enhance emotional intelligence among EFL students, highlighting its potential to safeguard against burnout. By illuminating these relationships, this study advocates for pedagogical strategies and institutional support that prioritize emotional intelligence, fostering the well-being and academic achievements of Chinese EFL students.